Method for forming ordered intermetallic compound on surface of shape-controllable core-shell structure
By depositing alloys on the palladium seed surface and performing low-temperature negative pressure heat treatment, the problem of catalyst activity loss in the prior art is solved, and the orderly phase transformation and morphology of the platinum-based catalyst is achieved, and the stability and activity of the catalyst are improved.
Patent Information
- Application Number
- CN202411687007.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-25
AI Technical Summary
In the prior art, it is difficult to achieve orderly phase transition of platinum-based catalysts while maintaining the original morphology and structure of the catalyst during high-temperature heat treatment, resulting in loss of catalyst activity and limited industrial application.
The alloy was deposited on the palladium seed surface by seed mediating method to form platinum-based core-shell nanoparticles, and loaded on a carrier, and short-term heat treatment was performed for negative pressure at 350-450°C to achieve orderly reconstruction of surface atoms.
While maintaining the original morphology and structure of nanoparticles, the formation of the surface orderly phase structure is achieved, the catalytic activity and stability of the catalyst are improved, and the morphological loss and particle size increase caused by high-temperature heat treatment are avoided.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of precious metal nanomaterials, and relates to a method for forming ordered intermetallic compounds on the surface of a morphology-controlled core-shell structure, and in particular to a method for achieving ordering of the surface of a morphology-controlled core-shell structure through low-temperature heat treatment. Background Art
[0002] Considering the dependence of catalytic reaction performance on catalyst structure and crystal plane, people have developed a variety of strategies to regulate the morphology and structure of catalysts. Among them, for the oxygen reduction reaction of the fuel cell cathode, the morphology-controlled platinum-based core-shell structure has been shown to effectively reduce the catalyst cost and improve the catalytic activity. However, the currently prepared platinum-based alloy shell is mainly an alloy phase. Since the arrangement of atoms in the alloy phase is random, the inevitable corrosion and precipitation of non-platinum transition metals during acidic electrochemical testing will cause the catalyst activity to lose, which seriously restricts the industrial application of the catalyst. Compared with random solid solution alloys, the arrangement of atoms in ordered intermetallic compounds follows certain rules and shows enhanced atomic bonding ability, thereby effectively improving the stability of the catalyst under service conditions. However, the ordering transformation of alloys is still limited to heat treatment under high temperature conditions, and the realization of alloy ordering transformation under high temperature conditions often sacrifices the original design size, morphology, structure and even high-performance crystal planes of nanomaterials.
[0003] Chinese patent application CN116652199A discloses a method for preparing platinum-cobalt intermetallic compound nanoparticles by direct heat treatment. This method can obtain ordered platinum-cobalt particles, but the catalyst carrier preparation process is complicated. At the same time, in order to obtain alloy particles first, the required heat treatment temperature is high and the time is long, resulting in the prepared alloy particles having no characteristic crystal planes exposed and uneven particle size. The heat treatment temperature in the subsequent ordering transformation is still higher than 550°C, causing further agglomeration of particles and changes in particle size. Chinese patent application CN118659004A discloses a method for preparing a tellurium-doped platinum-cobalt intermetallic compound catalyst. This method can obtain tellurium-doped platinum-cobalt intermetallic compound particles by a simple high-temperature annealing method after impregnation, but its heat treatment temperature is as high as 1000°C, which also results in the obtained particles having no characteristic crystal planes exposed. Chinese patent application CN115188979A discloses a method for preparing an ordered platinum-cobalt intermetallic oxide oxygen reduction catalyst. This method also utilizes a high-temperature annealing method after impregnation to prepare platinum-cobalt intermetallic compound nanoparticles. The heat treatment temperature used is higher than 700° C. The obtained particles have no specific morphology and are uneven in size.
[0004] Considering the important role of the catalyst surface in the catalytic reaction, it is of great significance to achieve precise control of the catalyst morphology, composition, phase and structure to improve the performance of the catalyst. Therefore, it is very important to develop a heat treatment method that can achieve the ordered phase transition of the platinum-based catalyst while maintaining the original crystal plane and structure and not changing the particle size. Summary of the invention
[0005] The purpose of the present invention is to provide a method for forming an ordered intermetallic compound on the surface of a morphology-controllable core-shell structure under low temperature conditions, so as to avoid the particle growth caused by the existing high-temperature heat treatment technology and the destruction of the particle morphology and structure, so as to obtain an ordered intermetallic compound phase while retaining the crystal plane with high catalytic performance for the oxygen reduction reaction at the cathode of the fuel cell.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The first aspect of the present invention provides a method for forming an ordered intermetallic compound on the surface of a morphology-controlled core-shell structure, comprising: depositing an alloy on the surface of a palladium seed by a seed-mediated method to obtain platinum-based core-shell nanoparticles, loading the platinum-based core-shell nanoparticles on a carrier, and then performing a short-time heat treatment under negative pressure at 350 to 450° C. to obtain core-shell particles with a maintained morphology and an ordered surface;
[0008] The metal component in the alloy is selected from at least one of Fe, Co or Cu and Pt.
[0009] The present invention has no restrictions on the core-shell composition, morphology, and preparation method of the platinum-based core-shell nanoparticles; the shell metal element in the platinum-based core-shell nanoparticles is selected from at least one of Fe, Co or Cu and Pt, and the core metal is Pd. The preparation methods of the platinum-based core-shell nanoparticles include slow deposition assisted by an injection pump and direct deposition.
[0010] The present invention realizes ordered reconstruction of surface atoms while maintaining the original special morphology and structure of the nanoparticles through a mild heat treatment technology, thereby obtaining platinum-based core-shell nanoparticles with an ordered phase structure on the surface and maintained morphology.
[0011] Furthermore, the seed-mediated method comprises: mixing palladium seeds, a reducing agent, and a metal component precursor, and heating the mixture in an organic solvent to react, thereby obtaining platinum-based core-shell nanoparticles;
[0012] The morphology of the platinum-based core-shell nanoparticles includes a cube, an octahedron, a hexapod, or a truncated octahedron.
[0013] In some specific embodiments, the seed-mediated method comprises:
[0014] Syringe pump-assisted slow deposition, i.e. slowly injecting the metal component precursor solution into an organic solvent containing palladium seeds and a reducing agent with the assistance of a syringe pump;
[0015] Direct deposition: Directly and quickly inject the metal component precursor solution into an organic solvent containing palladium seeds and reducing agents;
[0016] Conformal deposition of a Pt-based alloy shell on the surface of a Pd seed was achieved.
[0017] In some specific embodiments, the injection rate during the syringe pump-assisted slow deposition process is about 0.2 to 0.6 mL h -1 The preferred injection rate is 0.5 mL h -1 .
[0018] Furthermore, the reducing agent is glucose, the cobalt precursor is cobalt acetylacetonate, the iron precursor is iron acetylacetonate, the copper precursor is copper acetylacetonate, the platinum precursor is chloroplatinic acid, and the organic solvent is oleylamine.
[0019] Furthermore, the feed ratio of the palladium seed to the reducing agent, the cobalt precursor, and the platinum precursor is 2 mg: 20 mg: 2.5×10 -6 mol:7.5×10 -6 mol.
[0020] Furthermore, in the heating reaction, the reaction temperature is 200° C. and the reaction time is 0.5 h.
[0021] In some specific embodiments, the seed-mediated method includes: dispersing palladium seeds and glucose in oleylamine, slowly injecting a precursor solution pre-dissolved in oleylamine into the reaction solution through a syringe pump, note that the precursor solutions of the two metals are obtained by dissolving the acid or acetylacetonate of the corresponding metals in oleylamine, the reaction solution is kept warm at 180-220°C and stirred, then washed and centrifuged, and then dispersed in chloroform or n-hexane.
[0022] In some specific embodiments, the concentration of the cobalt precursor, the iron precursor, and the copper precursor in the metal component precursor solution is 0 to 0.002 mol L -1 The further preferred concentration is 0.001 mol L -1 ; The concentration of the platinum precursor in the metal component precursor solution is 0 to 0.006 mol L -1 The further preferred concentration is 0.002 mol L -1 .
[0023] In some specific embodiments, the concentration of the reducing agent in the reaction system is 5 to 10 mg mL -1 .
[0024] Furthermore, the alloy particles are loaded on the carrier by impregnation or blending and grinding.
[0025] Furthermore, in the impregnation, the impregnation method includes: ultrasonically dispersing the platinum-based core-shell nanoparticles and the carrier in chloroform, continuously stirring, centrifugally separating, and vacuum drying to obtain.
[0026] Furthermore, in the vacuum drying, the drying temperature is 50-60° C. and the drying time is 30-60 min.
[0027] Furthermore, the carrier is a carbon material or a conductive metal oxide.
[0028] Furthermore, the carbon material is one of amorphous carbon powder, graphitized carbon powder or carbon nanotubes.
[0029] As a preferred technical solution, the carbon material is Vulcan XC-72 amorphous carbon powder.
[0030] Furthermore, the mass ratio of the platinum-based core-shell nanoparticles to the carrier is (0.1-0.5):1; preferably the mass ratio is 0.25:1.
[0031] Furthermore, in the negative pressure short-time heat treatment, the treatment time is 2 to 20 minutes.
[0032] Furthermore, in the negative pressure short-time heat treatment, the treatment pressure is 10 -5 ~10 -1 Pa.
[0033] Furthermore, in the negative pressure short-time heat treatment, the heating rate is 5 to 30 °C min -1 .
[0034] As a more preferred technical solution, in the negative pressure heat treatment, the heat treatment pressure is 10 -3 Pa, heating rate is 20℃min -1 , the heat treatment temperature is 400℃, and the heat treatment time is 5min.
[0035] As a preferred technical solution, after the negative pressure heat treatment, direct air cooling is used to obtain core-shell particles with preserved morphology and ordered surface atoms.
[0036] As a preferred technical solution, after the negative pressure heat treatment, the collected platinum-based particles with controllable morphology and ordered core-shell structure surface can be stored for future use without any washing process.
[0037] The second aspect of the present invention provides an application of a method for forming an ordered intermetallic compound on the surface of a morphology-controlled core-shell structure, including using the method to prepare a cathode catalyst, and the cathode catalyst is used in a fuel cell.
[0038] Compared with the prior art, the present invention has the following characteristics:
[0039] The present invention first obtains morphology-controllable Pt-based core-shell nanoparticles by a seed-mediated method, then loads the particles onto a carbon carrier, and then uses a mild heat treatment method under low temperature conditions to transform the surface components (such as Figure 5 The ordered phase is formed on the surface of the particles without sacrificing the original special morphology and structure of the particles. The ordered reconstruction of the atoms on the surface of the metal nanoparticles under the low-temperature heat treatment can effectively avoid the morphology loss, agglomeration and particle size increase caused by Oswald ripening of the nanoparticles under high-temperature heat treatment. By retaining the designed crystal plane while obtaining the ordered phase, the catalytic activity and stability of the catalyst are effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Transmission electron microscope photo and composition analysis of cubic Pd@Pt-Co alloy particles prepared in step S1 of Example 1;
[0041] Figure 2 Transmission electron microscope photograph and composition analysis of cubic Pd@Pt-Co particles with surface ordered structure after heat treatment prepared in step S5 in Example 1. Figure 2 In (c), the blue balls represent platinum and the pink balls represent cobalt; Figure 2 The scale bars in (b, dg, hk) are all 0.5 nm.
[0042] Figure 3 The electrochemical performance test results of the cubic Pd@Pt-Co alloy particles prepared in step S1 of Example 1 and the cubic Pd@Pt-Co particles with a surface ordered structure after heat treatment prepared in step S5;
[0043] Figure 4 The electrochemical performance test results of commercial platinum-carbon catalysts;
[0044] Figure 5 Schematic diagram of the structural evolution of core-shell nanoparticles under low-temperature heat treatment in the present invention. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0046] The following are more detailed implementation cases, which further illustrate the technical solutions of the present invention and the technical effects that can be obtained.
[0047] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.
[0048] The Pd nanocube seeds in the following examples can be obtained according to the methods reported in published literature, for example: Xue S, Chen G, Li F, et al. Understanding of strain-induced electronic structure changes in metal-based electrocatalysts: using Pd@Pt core-shell nanocrystals as an ideal platform[J]. Small, 2021, 17(30): 2100559.
[0049] Shi F,Peng J,Li F,et al.Design of Highly Durable Core-Shell Catalystsby Controlling Shell Distribution Guided by In-Situ Corrosion Study[J].Advanced Materials,2021,33(38):2101511.
[0050] Embodiment 1:
[0051] A method for preparing a surface ordered intermetallic compound with a morphology controllable core-shell structure mainly comprises the following steps:
[0052] S1: Preparation of cubic Pd@Pt-Co alloy particles by liquid-phase seed-mediated method: 1.5 mL of oleylamine solution containing about 2 mg of Pd nanocube seeds with a size of 10 nm was added to 3.5 mL of oleylamine solution dissolved with 20 mg of glucose. The mixed solution was placed in a 25 mL single-necked flask and preheated at 200 °C for 5 min.
[0053] Then, the molar concentration was 0.001 mol L -1 and 0.003 mol L -1 The oleylamine solution of cobalt acetylacetonate and chloroplatinic acid hexahydrate was heated at 0.5 mL h -12.5 mL of the reaction solution was injected at an injection rate of . Then, stirring and heat preservation were continued at 200°C for 30 min. After the reaction was completed, the sample was washed three times with chloroform and ethanol, and the sample cubic Pd@Pt-Co alloy particles were redispersed in chloroform and stored for later use.
[0054] S2: The obtained cubic Pd@Pt-Co alloy particles were loaded onto Vulcan XC-72 amorphous carbon powder. The mass ratio of cubic Pd@Pt-Co alloy particles to Vulcan XC-72 amorphous carbon powder was 0.25:1. The particles and Vulcan XC-72 amorphous carbon powder were uniformly dispersed in chloroform by ultrasound. After stirring at room temperature for 10 hours, the carbon-supported cubic Pd@Pt-Co alloy particle sample was obtained by high-speed centrifugation. The sample was then dissolved in n-butylamine solution again, stirred at room temperature for 3 days for degreasing, and then a surface-cleaned sample was obtained by high-speed centrifugation and methanol washing. It was then dried in a vacuum oven at 60°C for 30 minutes.
[0055] S3: The dried carbon-supported cubic Pd@Pt-Co alloy particle sample was spread flat on a quartz boat and placed in a vacuum tube furnace. The vacuum tube furnace was evacuated for a long time by a vacuum pump until the pressure in the vacuum reactor reached 10 -3 Pa.
[0056] S4: After the pressure in the furnace tube stabilizes, -1 The heating rate was increased to 400 °C, and the carbon-supported cubic Pd@Pt-Co alloy particle sample was subjected to constant temperature heat treatment for 5 min. After that, the furnace cover was opened and directly air-cooled.
[0057] S5: After the sample cools down to room temperature, the solid powder in the quartz boat is collected, and the obtained cubic Pd@Pt-Co particles with surface ordered structure can be used without any post-treatment.
[0058] Application Example 1:
[0059] This example is used to characterize and analyze the samples prepared in Example 1, and the results are as follows:
[0060] Figure 1 The transmission electron microscope photo and composition analysis of the cubic Pd@Pt-Co alloy particles prepared in step S1 of Example 1 show that the Pt-Co alloy shell is uniformly deposited on the surface of the Pd seed to form a core-shell structure. At the same time, the uniform contrast distribution in the transmission electron microscope photo shows that the particles present a random solid solution structure of the alloy.
[0061] from Figure 2It can be seen that the Pd@Pt-Co prepared in step S5 after heat treatment still maintains the cubic morphology and core-shell structure well. At the same time, regular contrast changes are observed in the catalyst surface area, showing the atomic arrangement characteristics of the typical ordered phase structure. Furthermore, the composition analysis of the ordered area corresponding to the atomic level shows that compared with the Pt-Co composition before heat treatment, the surface after heat treatment is a (Pt, Pd)-Co ternary system.
[0062] Application Example 2:
[0063] This example is used to test the oxygen reduction performance of the cubic Pd@Pt-Co particles with a surface ordered structure prepared in Example 1. The test method includes:
[0064] The catalyst sample was prepared into a uniform slurry: 5 mg catalyst, 4 mL deionized water, 1 mL isopropanol, and 25 μL Nafion solution were mixed evenly, and then ultrasonicated in an ice-water bath for 30 min to obtain a uniform slurry;
[0065] The uniform slurry containing about 4 μg of Pt was added dropwise to a 0.196 cm 2 On the glassy carbon electrode, the test was carried out after natural drying;
[0066] The three-electrode test method is adopted, with the glassy carbon electrode loaded with catalyst as the working electrode, the platinum wire as the counter electrode, and the reversible hydrogen electrode (RHE) as the reference electrode. During the stability test, due to the long test time, the reference electrode can be replaced with a silver / silver chloride electrode.
[0067] In Ar-saturated 0.1 M HClO 4 A 0.05-1.0 V / RHE voltammetric cyclic scanning test was performed in aqueous solution;
[0068] In CO saturated 0.1 M HClO 4 CO was adsorbed in aqueous solution at 0.2 V / RHE, and then in Ar-saturated 0.1 M HClO 4 CO desorption test was carried out in aqueous solution at 0.05-1.2V / RHE;
[0069] In O 2 Saturated 0.1M HClO 4 The polarization curve test of 0-1.1V / RHE was carried out in aqueous solution.
[0070] Combining the voltammetric cycle curves, CO desorption curves and polarization curves, the oxygen reduction activities of the catalysts can be compared.
[0071] An accelerated stability test was performed over 30,000 cycles in the voltage range of 0.6-1.0 V / RHE, followed by an oxygen reduction performance test to evaluate the stability of the catalyst.
[0072] The results are as follows:
[0073] from Figure 3 , Figure 4 It can be seen that the cubic Pd@Pt-Co particles with an ordered surface structure obtained after heat treatment (denoted as annealed Pd@Pt-Co in the figure) show enhanced activity and stability compared to the original Pd@Pt-Co particles (the product obtained in step S1 of Example 1, denoted as Pd@Pt-Co in the figure) and the commercial platinum carbon catalyst (denoted as Pt / C in the figure). The mass activity of the Pd@Pt-Co sample after heat treatment is 1.1 times and 2.1 times that of the original Pd@Pt-Co particles and commercial Pt / C, respectively. The cubic Pd@Pt-Co particles with an ordered surface lost about 40% of their mass activity after the accelerated stability test, while the mass activity loss of the original particles was as high as 81%.
[0074] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for forming an ordered intermetallic compound on the surface of a morphology-controlled core-shell structure, characterized in that: The method comprises: depositing an alloy on the surface of a palladium seed by a seed-mediated method to obtain platinum-based core-shell nanoparticles, loading the platinum-based core-shell nanoparticles on a carrier, and then performing a short-time heat treatment under negative pressure at 350 to 450° C. to obtain core-shell particles with a maintained morphology and an ordered surface; The metal component in the alloy is selected from at least one of Fe, Co or Cu and Pt.
2. The method for forming an ordered intermetallic compound on the surface of a morphology-controlled core-shell structure according to claim 1, characterized in that: The seed-mediated method comprises: mixing palladium seeds, a reducing agent, and a metal component precursor, and heating and reacting them in an organic solvent to obtain platinum-based core-shell nanoparticles; The morphology of the platinum-based core-shell nanoparticles includes a cube, an octahedron, a hexapod, or a truncated octahedron.
3. The method for forming a surface ordered intermetallic compound with a morphology-controlled core-shell structure according to claim 2, characterized in that: The reducing agent is glucose, the cobalt precursor is cobalt acetylacetonate, the iron precursor is iron acetylacetonate, the copper precursor is copper acetylacetonate, the platinum precursor is chloroplatinic acid, and the organic solvent is oleylamine; Preferably, the feed ratio of the palladium seed, the reducing agent, the cobalt precursor, and the platinum precursor is 2 mg: 20 mg: 2.5×10 -6 mol:7.5×10 -6 mol.
4. The method for forming an ordered intermetallic compound on the surface of a morphology-controlled core-shell structure according to claim 2, characterized in that: In the heating reaction, the reaction temperature is 200° C. and the reaction time is 0.5 h.
5. The method for forming an ordered intermetallic compound on the surface of a morphology-controlled core-shell structure according to claim 2, characterized in that: The platinum-based core-shell nanoparticles are loaded on a carrier by impregnation or blending and grinding; In the impregnation, the impregnation method includes: ultrasonically dispersing the platinum-based core-shell nanoparticles and the carrier in chloroform, continuously stirring, centrifugally separating, and vacuum drying to obtain; The carrier is a carbon material or a conductive metal oxide.
6. The method for forming an ordered intermetallic compound on the surface of a morphology-controlled core-shell structure according to claim 5, characterized in that: The carbon material is one of amorphous carbon powder, graphitized carbon powder or carbon nanotubes.
7. The method for forming an ordered intermetallic compound on the surface of a morphology-controlled core-shell structure according to claim 5, characterized in that: The mass ratio of the platinum-based core-shell nanoparticles to the carrier is (0.1-0.5):
1.
8. The method for forming an ordered intermetallic compound on the surface of a morphology-controlled core-shell structure according to claim 1, characterized in that: In the negative pressure short-time heat treatment, the treatment time is 2 to 20 minutes.
9. The method for forming an ordered intermetallic compound on the surface of a morphology-controlled core-shell structure according to claim 1, characterized in that: In the negative pressure short-time heat treatment, the treatment pressure is 10 -5 ~10 -1 Pa.
10. An application of the method for forming ordered intermetallic compounds on the surface of a morphology-controlled core-shell structure as claimed in any one of claims 1 to 9, characterized in that: The method is used for preparing a cathode catalyst, and the cathode catalyst is used for a fuel cell.
Citation Information
Patent Citations
Ordered platinum-cobalt intermetallic compound oxidation catalyst as well as preparation method and application thereof
CN115188979A
Method for preparing platinum-cobalt intermetallic compound nanoparticles through direct heat treatment
CN116652199A
Preparation method and application of tellurium-doped platinum-cobalt intermetallic compound catalyst
CN118659004A
Octahedral palladium-platinum core-shell catalyst preparation method
CN108630948A
Preparation method of three-dimensional carrier supported platinum-palladium-cobalt alloy structure catalyst for low-temperature fuel cell
CN109873174A
Cited By
Universal preparation method of morphology-controllable ordered alloy nanocrystals based on unbalanced nano-metallurgy strategy
CN122252631A